Wavelength-stabilized DBR high-power diode laser. (28th January 2020) - Paoletti, R; Coriasso, C; Meneghini, G; Gaziano, F; Gotta, P; Codato, S; Maina, A; Morello, G; De Melchiorre, P; Pippione, G; Riva, E; Rosso, M; et al.
Abstract: This paper reports a wavelength-stabilized high-power diode laser emitting up to 14 W CW in the 9xx nm range. Wavelength stabilization is achieved by a distributed Bragg reflector (DBR) monolithically integrated in the diode laser chip. Key features are identical layer epitaxy (ILE) and the use of a multiple-order electron beam lithography (EBL) optical confining grating. ILE avoids any regrowth or complex technology processes, while EBL multiple-order grating allows narrow-band back reflection and effective lateral optical confinement, and makes it possible to stabilize multiple wavelengths on the same wafer using a manufacturable and reliable technology. DBR diode lasers with different pitches, whose wavelengths were 3 nm spaced, were fabricated and high spectral purity (95% optical power within about 0.6 nm) and wavelength stability were measured. Moreover, the high uniformity of performances across the wafer with different emitted wavelengths demonstrates the maturity of the proposed technology for high-yield, high-volume laser diode production for wavelength-stabilized applications. A multi-emitter module, including ten DBR diode lasers, collimating and focusing optics, showed 100 W CW wavelength-stabilized output power at 14 A in a 135 μ m core optical fiber within 0.17 NA. Single diode lasers, or multi-emitter modules, can be used to combine high-power optical beams by wavelength division multiplexing (WDM) using dichroic optics, scaling up beam power to the kW range and maintaining optical beam quality.